The Role of Laboratories and Simulators in the Achievement of Competency Graduates of the Diploma IV Program of the Makassar Polytechnic of Shipping Sciences - Agustina Setyaningsih; Ahmad Wahid; Rahmat Hidayat; Napsawati Napsawati; Pinrapati Wajuana (PT Publikasiku Academic Solution, 2025)
This study examines the role of laboratories and simulators in achieving competency outcomes among graduates of the Diploma IV program at the Politeknik Ilmu Pelayaran Makassar (PIP Makassar). As a vocational institution under the Ministry of Transportation, PIP Makassar implements 60-70% practical learning to prepare skilled maritime professionals. However, preliminary evaluations indicate challenges in students' technical skill mastery and workplace adaptation despite high graduate employment rates. Using an exploratory sequential mixed-methods design, this research involved 295 student respondents and lecturers/instructors as key informants. Data were collected through questionnaires, interviews, observations, and documentation of practical exam scores. The findings reveal that student competency achievement falls predominantly in the medium (41.69%) and high (35.25%) categories. Simple regression analysis demonstrates a significant positive relationship between laboratory and simulator utilization and graduate competency ( ; Beta = 0.620; Sig. = 0.001), indicating that increased facility use enhances competency outcomes. However, obstacles persist, including limited practice time, insufficient equipment modernization, suboptimal instructor guidance, inconsistent teaching methods, and gaps between theoretical knowledge and practical application. Key recommendations include extending practice hours, modernizing facilities, integrating real-world case scenarios, restructuring the curriculum to increase practical portions, providing continuous instructor training, and implementing competency-based assessment systems with clear feedback mechanisms. This study contributes to maritime vocational education by providing evidence-based strategies for optimizing laboratory and simulator utilization to meet international maritime standards and industry demands.